Micro-inverter for integrated grid-tie photovoltaic module using resonant controller - Gazoli, Jonas Rafael; Villalva, Marcelo Gradella [UNESP]; Ruppert, Ernesto (Wiley-Blackwell, 2014)
Two-stage isolated converters for photovoltaic (PV) applications commonly employ a high-frequency transformer (HFT) on the DC-DC side, submitting the DC-AC inverter switches to high voltages and forcing the use of insulated-gate bipolar transistors instead of low-voltage and low-loss metal-oxide-semiconductor field-effect transistors. This paper shows the modeling, control and simulation of a single-phase full-bridge inverter with HFT that can be used as part of a two-stage converter with transformerless DC-DC side or as a single-stage converter (simple DC-AC inverter) for grid-connected PV applications. The inverter is modeled to obtain a small-signal transfer function used to design the P+Resonant current control regulator, whose main advantages are the simplicity for implementation in single-phase systems and zero steady state error with sinusoidal current. A high-frequency step-up transformer results in low-voltage switches and better efficiency compared with converters in which the transformer is used on the DC-DC side. Simulations and experimental results with a 200-W prototype are shown.
Keywords: grid-connected; full-bridge inverter; high-frequency transformer; modeling; P plus Resonant; photovoltaic